Corrosion Properties of Electropolished AISI 316L Austenitic Biomaterial in Relation to Electropolishing Conditions - Viera ZATKALÍKOVÁ (Kaunas University of Technology, 2021)
Electropolishing is recommended for various biomedical applications of austenitic biomaterials because it enables to achieve high brightness, very low surface roughness, excellent corrosion resistance and reduced bacterial attachment without residual surface tensions. The quality of an electropolished surface depends strongly on the composition of used electrolyte and on the applied electropolishing conditions. In this article the corrosion properties of eight AISI 316L surfaces electropolished in the same solution but at the different conditions were evaluated on the bases of the electrochemical impedance spectroscopy (EIS) test and exposure immersion test. The aim was to find whether in the frame of recommended electropolishing conditions (temperature, current density, time) the optimal combination exists which would provide the best corrosion properties of the surface passive film. The results showed that the electropolishing temperature 50 ºC should be preferred due to the lower roughness parameters and minimizing the possibility of the bacterial attachment.